Involvement of 5-Serotonin and Substance p Pathways in Dichroa Alkali Salt-Induced Acute Pica in Rats - Ma, Lina; Li, Sidi; Li, Jian; Zhang, Guangping; Hou, Hongping; Ye, Zuguang (Frontiers in Pharmacology, 2021)
Dichroa alkali salt (DAS) is the active ingredient of Changshan, a traditional Chinese antimalarial medicine. However, owing to its vomiting side effects, its use is limited. Recently, DAS-induced vomiting has attracted broad attention; however, the mechanisms involved have not yet been elucidated. The present study aimed to explore DAS induced vomiting and decipher the potential role of the 5-serotonin (5-HT) and substance P (SP) signaling pathways. We used a combination of approaches in the context of a rat pica model, such as immunoblot analysis, HPLC-ECD, ELISA, quantitative real-time PCR, pharmacological inhibition, and immunohistochemistry assays. We demonstrated that DAS contributed to Changshan-induced vomiting via the activation of the 5-HT and SP signaling pathways. DAS could induce a dose-dependent kaolin intake in the rat pica model. Moreover, DAS caused a similar profile as Cisplatin (DDP): “low-dose double-peak, high-dose single-peak pica phenomenon”. Interestingly, treatment with DAS stimulated the peripheral ileum and central medulla oblongata and augmented the release of 5-HT, SP, and preprotachykinin-A and the expression of 5-HT3 and NK1 receptors in the two issues. Additionally, the 5-HT3 and NK1 receptor antagonists effectively alleviated DAS-induced kaolin intake and significantly reduced DAS-induced 5-HT and SP levels in the ileum and medulla oblongata. Similar responses were not observed in the context of dopamine receptor inhibition. This study innovatively revealed that the 5-HT and SP-mediated vomiting network plays an important role in DAS-induced vomiting; of note, ondansetron and aprepitant can effectively antagonize DAS-induced vomiting. Our results suggest a potential therapeutic strategy (based on drugs approved for human use) to prevent the DAS-associated adverse reactions.